Factor Mobility and Dispersion in Marginal Products: A Case on China - Liutang Gong; Danyang Xie (Frontiers of Economics in China-Selected Publication from Chinese Universities, 2006)
This paper examines the efficiency in resource allocation in China. We estimate production functions at the provincial level and use these functions to compute time series for marginal products of capital and labor. We found that dispersion in the marginal product of capital declined from 1970 to 1984 and then became stable afterward, whereas the dispersion in the marginal product of labor declined initially but the trend has been reversed since 1993. We argue that this reversal may indicate any of the following: (1) policy-driven labor migration adding to labor market inefficiency; (2) the presence of increasing returns in labor; and (3) both capital and labor having become mobile since 1993.